MEDIA SMART BOX ZAKAT: SOLUSI INOVATIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SD NEGERI PLERET KIDUL - Budiarti, Diah; Mhd. Lailan Arqam; Hanif Cahyo Adi Kistoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in the zakat material of class V of SD Negeri Pleret Kidul, where 73% of students have not reached the Minimum Completeness Criteria (KKM). These problems are caused by conventional learning and the lack of use of interactive media. This research aims to develop Smart Box Zakat learning media that is suitable for use in learning. This research is a Research and Development (R&D) with a 4D (Define, Design, Develop, Disseminate) model. The Define stage includes an analysis of students' needs, characteristics, and materials. The Design stage includes media design and instrument preparation. The Develop stage is carried out through product creation and validation by media, material, and language experts. The Disseminate stage is carried out on a limited basis to PAI teachers throughout Kapanewon Panjatan. The research instruments were in the form of validation questionnaires and teacher response questionnaires. The data was analyzed descriptively quantitatively. The results of the study showed that the media obtained a feasibility percentage above 90% with a very feasible category, and received a very good response from teachers. Thus, Zakat Smart Box Media is suitable for use as a learning medium for zakat materials for grade V elementary school.